Polypeptides having peroxygenase activity and polynucleotides encoding same - OESTERGAARD LARS HENRIK; KALUM LISBETH; LANDVIK SARA (2014)
The present invention relates to isolated polypeptides having peroxygenase activity, and polynucleotides encoding the polypeptides. The invention also relates to nucleic acid constructs, vectors, and host cells comprising the polynucleotides as well as methods of producing and using the polypeptides.